The epidemiology of S. sonnei and S. flexneri in Pima County, Arizona: an exploratory study. - McCombie, S C (1988)
Investigation of 189 cases of shigellosis reported to the Pima County, Arizona Health Department in 1986 revealed that 23 per cent of cases could be attributed to travel to Mexico, and 10 per cent to day care attendees and their household contacts. No source of infection or high-risk activity could be demonstrated for 43 per cent of the cases. Households in which S. flexneri occurred were more likely to be characterized by crowded living situations and to have no known source of infection.